As redes de forma????o de professores a dist??ncia sob a interpreta????o dos gestores do sistema UAB - Gon??alves, D??bora Costa (2017)
The purpose of this study was to investigate how the interpretation of the policy of distance teacher training of the UAB System and its governance networks occurs in the perspective of the managers who work in the public higher education institutions that are part of the program. It???s a qualitative study inspired by the Policy Cycle method (BOWE; BALL; GOLD, 1992; BALL, 1994). Were used as research techniques: documentary analysis, questionnaire and interviews with UAB managers of the Public Institutions of Higher Education (IPES). The data were analyzed in light of the theory of Content Analysis of Bardin (2011) and discussed in three categories: Interpretation of managers about distance education (EaD) and its governance networks; Institutional impacts of UAB in the practice context in the program participating IPES; and Prospects for distance teacher education policies: beyond UAB. The results showed that the conceptions underlying the UAB managers' training model are in line with the hegemonic proposals of teacher training. There is no perception of the influence of entities of the network of governance as private sector and international organizations. In the institutional practical context, the EAD has promoted a 'differentiation' between professionals and students within IPES. The consolidation of the EAD courses in IPES brings with it the appropriation of new perceptions, values and practices for these entities. There was an obscuring between the frontiers of teacher, tutor and student performances, and the gradual naturalization of the precariousness of teaching work. Regarding the perspectives for training by the UAB, the consolidation of the EAD in the IPES is envisaged. The research concludes that teacher education is immersed in an extremely complex context of political, economic and ideological disputes, and that the expansion of EaD takes place in a scenario where multiple interests compete for a cheap, lightened, massified and privatized formation. Thus, we propose the questioning of the MEC and Capes of intensive use for initial teacher training. More in-depth discussions should integrate the questionings of EaD professionals, so that the modality is not instrumentalized for a mass training process, neotechnicist, mechanism of precarization of teaching work. In addition, we propose extending the autonomy of the IPES with a more strategic position by the federal government.